2013
DOI: 10.7150/ijms.5181
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Subclinical Atherosclerosis in Diabetic and Obese Children

Abstract: Background. Increased carotid intima-media thickness (cIMT) is considered a marker of early-onset atherosclerosis and it seems to predict cardiovascular events both in obese and diabetic subjects. We aimed to evaluate early signs of atherosclerosis and investigate for predisposing factors in children and adolescents affected by type 1 diabetes (T1DM) or obesity, comparing them with healthy controls.Methods. Out of 71 enrolled subjects (mean age 12.8 ± 2.3 years), 26 had T1DM and 24 were obese, while 21 age- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…It is also recommended by the American Heart Association as a noninvasive imaging parameter for detecting atherosclerosis [9,10]. Previous studies reported that cIMT correlates with high insulin levels (a sign of IR) in obese patients and with high fasting glucose levels (a sign of relative insulin deficiency) in subjects with type 1 diabetes [11]. Moreover, other ultrasound parameters have been associated with cardiovascular risk in obese subject [12].…”
Section: Introductionmentioning
confidence: 98%
“…It is also recommended by the American Heart Association as a noninvasive imaging parameter for detecting atherosclerosis [9,10]. Previous studies reported that cIMT correlates with high insulin levels (a sign of IR) in obese patients and with high fasting glucose levels (a sign of relative insulin deficiency) in subjects with type 1 diabetes [11]. Moreover, other ultrasound parameters have been associated with cardiovascular risk in obese subject [12].…”
Section: Introductionmentioning
confidence: 98%
“…High sensitivity C-reactive protein (CRP) is the most studied inflammatory marker in pediatric type 1 diabetes. In healthy adults, CRP levels predict future cardiovascular disease and are linked to endothelial dysfunction [1315], Most [6, 7, 1622], but not all studies [23, 24], have demonstrated significant increases in CRP levels in pediatric T1D patients. Soluble intracellular adhesion molecule 1 (sICAM 1) is biochemical marker of endothelial damage and inflammation and is again elevated in pediatric T1D [7, 20, 2527].…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of childhood obesity are because of the increase in meta-children, thus becoming more susceptible to cardiovascular events in adult life 16) . Furthermore, other studies have demonstrated that cIMT correlates with high insulin levels in obese patients 17,18) .…”
Section: Introductionmentioning
confidence: 99%